“Implementación de un aplicativo web para el registro de calificaciones de los proyectos de investigación de la Universidad Técnica de Cotopaxi - Extensión La Maná”. - Bravo Pérez, Amaro Roy (2023)
The purpose of this research project is the implementation of a web application at the Technical University of Cotopaxi - La Maná Extension to register the grades of research projects. For this purpose, the PHP programming language is used to create web pages and to install a group of applications 1) Web Server: Apache, 2) PHP module or interpreter, and 3) Database Server: MySQL. MySQL allows storing, accessing, and replicating data through multiple storage engines, which implement a user-server model. To fulfill this purpose was applied formative and field research, bibliographic, inductive, and deductive methods, and the quantitative approach. The research was based on the population universe of 64 teachers by applying the sampling formula resulted in 10 teachers who were the survey respondent. The results of this research indicated that the registration of grades of the research projects is carried out in a physical form, handwritten or in traditional spreadsheets, without any organization and control, making the registration process slow and not organized. Thus, the proposal focuses on an application to register the grades of research projects at the Technical University of Cotopaxi - La Maná Extension.